TOXICITY TEST OF Eusideroxylon zwageri BARK EXTRACT BASED ON LIVER HISTOPATHOLOGY HYDROPIC DEGENERATION AND NECROSIS - Dhiya Salma Azminida; I Wayan Arya Krishnawan Firdaus; Juliyatin Putri Utami; Beta Widya Oktiani; Erida Wydiamala (FKG ULM, 2024)
Background: Ironwood bark extract contains antioxidant properties such as flavonoids, phenolics, and proanthocyanidins, which can stabilize ROS in the body and help accelerate wound healing. The liver plays a role in nutrient metabolism, detoxification, and ROS production. The lack of antioxidants to neutralize excess ROS makes the liver vulnerable to damage. Purpose: This study aimed to determine that there was no toxic effect of giving ironwood bark extract (Eusideroxylon zwageri) doses of 1.250 mg/kg, 2.750 mg/kg, and 4.750 mg/kg on the liver of Wistar rats based on histopathological features of hydropic degeneration and necrosis. Methods: Pure laboratory experimental quantitative (true experimental) with a post-test-only research design with control group design and One Way Anova statistical test. Treatment was given to 4 groups, namely group (K) was given aquadest control, group (T1) was given ironwood bark extract at a dose of 1.250 mg/kgBW, group (T2) was given ironwood bark extract at a dose of 2.750 mg/kgBW, and group (T3) given ironwood bark extract at a dose of 4.750 mg/kgBW. Results: The results showed no significant difference between the four treatment groups based on the average percentage of hydropic degeneration and necrosis. Conclusion: There was no toxic effect of giving ironwood bark extract doses of 1.250 mg/kgBW, 2.750 mg/kgBW, and 4.750 mg/kgBW on the liver of Wistar rats based on histopathological appearance of hydropic degeneration and necrosis for 14 days.